2016
DOI: 10.2147/ndt.s104450
|View full text |Cite
|
Sign up to set email alerts
|

White matter alterations related to attention-deficit hyperactivity disorder and COMT val158met polymorphism: children with valine homozygote attention-deficit hyperactivity disorder have altered white matter connectivity in the right cingulum (cingulate gyrus)

Abstract: IntroductionIn this article, the COMT gene val158met polymorphism and attention-deficit hyperactivity disorder (ADHD)-related differences in diffusion-tensor-imaging-measured white matter (WM) structure in children with ADHD and controls were investigated.Patients and methodsA total of 71 children diagnosed with ADHD and 24 controls aged 8–15 years were recruited. Using diffusion tensor imaging, COMT polymorphism and ADHD-related WM alterations were investigated, and any interaction effect between the COMT pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 70 publications
(101 reference statements)
0
12
0
Order By: Relevance
“…An important function of this bundle is related to the communication between components of the limbic system ( Mufson and Pandya, 1984 ) as well as with the execution of top-down and bottom-up attentional signals ( Bonnelle et al, 2012 ). Disconnection of this fiber bundle has been associated with post-traumatic amnesia ( De Simoni et al, 2016 ), with attention-deficit hyperactivity ( Kabukcu Basay et al, 2016 ) and with Alzheimer's disease ( Lee et al, 2015 ). We also found an association between increases in RD in the ILF and impaired performance on the Symbol Digit.…”
Section: Discussionmentioning
confidence: 99%
“…An important function of this bundle is related to the communication between components of the limbic system ( Mufson and Pandya, 1984 ) as well as with the execution of top-down and bottom-up attentional signals ( Bonnelle et al, 2012 ). Disconnection of this fiber bundle has been associated with post-traumatic amnesia ( De Simoni et al, 2016 ), with attention-deficit hyperactivity ( Kabukcu Basay et al, 2016 ) and with Alzheimer's disease ( Lee et al, 2015 ). We also found an association between increases in RD in the ILF and impaired performance on the Symbol Digit.…”
Section: Discussionmentioning
confidence: 99%
“…Met-carriers exhibited smaller striatal GMV than the Val-Val genotype ( Shimada et al, 2017 , p. 2), while Val-Val ADHD-diagnosed children had significantly lower fractional anisotropy and higher radial diffusivity in the cingulate gyrus compared to ADHD-diagnosed Met-carriers ( Basay et al, 2016 ). Also, white matter connections in Met-allele carriers were weaker than those in Val-Val-allele carriers ( Hong et al, 2014 ).…”
Section: Methodsmentioning
confidence: 87%
“…Several studies have shown that COMT and BDNF polymorphisms were more common in psychiatric patient groups compared to the general population. [1223242526] In our previous study performed in panic disorder patients, we found an important association in COMT Met/Met genotype in patients according to controls. [26] In the study of Šberg et al ., it is found that depressed patients had higher frequency of COMT Met/Met (LL) genotype.…”
Section: Discussionmentioning
confidence: 92%
“…COMT has also a role in drug metabolism including catechol used for the treatment of many diseases such as asthma and Parkinson's disease. [12131415] The monoamines, epinephrine, norepinephrine, serotonin, and tyramine, may play a role in the pathophysiology of paraphilias. These neurotransmitters are neuromodulators having effects on memory, motivational behavior, appetite, and sexuality of people.…”
Section: Introductionmentioning
confidence: 99%